Studying the “Gnostic Bible”: Samael Aun Weor and the Pistis Sophia - Winter, Franz (International Journal for the Study of New Religions, 2018)
In 1983, a book entitled El Pistis Sophia Develado (Pistis Sophia Unveiled) by the Colombian esoteric writer Samael Aun Weor, born Víctor Manuel Gómez Rodríguez (1917-1977), was published posthumously. It is considered a commentary to an important ancient Gnostic text, Pistis Sophia, that is read according to the Neo-Gnostic teachings of the author. This article provides insight into Weor's specific approach to this text and the "Procrustean bed" of interpretation he applied to it.